2013
DOI: 10.1016/j.jflm.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Fatal intimate partner violence against women in Portugal: A forensic medical national study

Abstract: Intimate partner violence (IPV) is an important cause of women's health and socio-familial severe problems, the most extreme being the victims' homicide. This is the first nationwide Portuguese autopsy-based and judicial-proven study about female intimate partner homicide.At least 62 women over 15 years old were killed by current or former men-intimate partners, corresponding to an IPV-related female mortality rate of 0.44/100.000 women; intimate partner violence was the reason of homicide in 60.8% of all auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
42
4
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 37 publications
10
42
4
7
Order By: Relevance
“…The remainder cases (n= 21, 7.4%) were attended at outpatient services. Medical assistance for IPV events mostly occurred at night (n= 109, 38.5% of cases) and in the afternoon (n = 81, 28.6%), especially during weekends (n= 107, 48.5%), which is in accordance with previous data 38,64 . This may be related to social customs including alcohol and drug consumption during the weekends 38,79 .…”
Section: Characteristics Of the Abuse And The Documented Injuriessupporting
confidence: 92%
See 1 more Smart Citation
“…The remainder cases (n= 21, 7.4%) were attended at outpatient services. Medical assistance for IPV events mostly occurred at night (n= 109, 38.5% of cases) and in the afternoon (n = 81, 28.6%), especially during weekends (n= 107, 48.5%), which is in accordance with previous data 38,64 . This may be related to social customs including alcohol and drug consumption during the weekends 38,79 .…”
Section: Characteristics Of the Abuse And The Documented Injuriessupporting
confidence: 92%
“…Alcohol or drugs were involved in the incident in 42.4% (n= 247) of cases. Most of abusive incidents were witnessed (n= 355, 61%), which is similar to other studies64 .Furthermore, an important number of violent events (n= 165, 28.3%) occurred in presence of minors, which is in agreement with previous research 65,66 . These children must be considered potential targets of protection and prevention measures because exposure to IPV during childhood increases the risk of being injured, of suffering serious psychological disturbance and also of becoming perpetrators or victims of that situations of IPV against women also affect children who are considered direct or indirect victims of this violence.…”
supporting
confidence: 91%
“…The absence of gunshot wounds in our cohort is typical for Finland [17]. In several other countries including the United States, firearms represent the most commonly used weapon in homicides, while a Portuguese study found that firearms most commonly cause IPV fatalities [18,19]. In Finland, however, firearm-related violence is rare; homicides occur in 40 % of cases through the use of sharp instruments, and more often when the perpetrator is female [16,17].…”
Section: Discussionmentioning
confidence: 89%
“…Con relación a los factores de riesgo, la violencia previa contra la víctima se considera el principal, razón por la cual una parte muy importante de las víctimas de homicidio habían sufrido previamente episodios de violencia (Campbell et al, 2003;Campbell, Glass, Sharps, Laughon y Bloom, 2007;Garcia et al, 2007;Pereira et al, 2013). Así, muchos autores señalan cómo los IPH son muchas veces una consecuencia extrema y no planificada de las relaciones abusivas previas (Cerezo, 1998;Norman y Bradshaw, 2013;Wilson y Daly, 1993).…”
Section: Marco Teóricounclassified
“…Como señalan diferentes autores, la interacción entre la violencia de género y la inmigración es una línea de investigación emergente y resulta recomendable profundizar en su estudio (Menjívar y Salcido, 2002;Raj y Silverman, 2002;Vives-Cases et al, 2009). Si bien existe una amplia literatura sobre la violencia en la pareja, el fenómeno del homicidio del compañero sentimental o intimate partner homicide (en adelante IPH) no ha recibido la misma atención por la comunidad científica internacional (Aldridge y Browne, 2003;Dobash, Dobash y Cavanagh, 2009;Hoyle, 2008;Pereira et al, 2013), sucediendo esto también en el caso específico de la población inmigrante. Así mismo, a pesar de la tendencia actual por parte de los investigadores a identificar los factores de riesgo del IPH (Aldridge y Browne, 2003;McFarlane et al, 1999), éstos no se han analizado de forma exclusiva en parejas inmigrantes (Messing, Amanor-Boadu, Cavanaugh, Glass y Campbell 2013).…”
unclassified